(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Neonatal Gastric Perforation is a rare but life threatening condition. Its incidence is reportedly to be 1 in 5000 live births. In most cases, the underlying cause could not be precisely determined. Prematurity, low birth weight, mechanical stress, and male gender are important factors. Objectives: The objective of this study is to share the experience of neonatal gastric perforation in Dhaka Shishu Hospital with regard to etiology, clinical presentation and surgical outcome. Materials and Methods: This retrospective study of seven neonates with Gastric Perforation was carried out at Dhaka Shishu Hospital from July 2008 to June 2011. The data reviewed included birth weight, gestational age at birth, age at presentation, clinical manifestations, pathological findings and outcome. Results: There were 5 male and 2 female neonates among them 3 were mature and 4 were premature. The average birth weight was 2.67 kg. Associated anomalies were present in 2 neonates (28.57%). Four patients had perforations in the greater curvature of stomach (57.14%), 2 in the anterior wall (28.57%), and 1 in the posterior wall (14.28%). The overall mortality in our series was 57.14%. The overall mortality of reported series was 48.91%. Among them thirty three were premature with 75.75% mortality, and 59 were term neonates with 33.89% mortality. Conclusion: Premature and low birth weight neonates are at increased risk of gastric perforation as well as mortality from it. Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 34-37